Towards a Framework of Culturally Responsive Boarding - Simone Healey; Glenn Auld (2024)
First Nations students from remote communities frequently make the choice to move to boarding school to complete their secondary education because of the limited educational opportunities in their local communities. To do this, students leave their family and peer support structures during adolescence. Although governments have provided funding for First Nations students to attend boarding school long before the Closing the Gap targets were set, outcomes of boarding for many of these students continue to disappoint, with low retention rates and below-average academic outcomes. Building on the principles of Culturally Responsive Pedagogy, a Culturally Responsive Boarding framework is proposed that reflects the unique needs of remote First Nation students. A rapid review included 21 peer reviewed articles about First Nations student experiences at boarding schools. The results were thematically coded to reveal that five Culturally Responsive Pedagogy strands were evident in the experiences of First Nations boarding students: having sociocultural consciousness; affirming views of students; acting as agents of change; learning about students and their communities; and culturally responsive teaching practices. Three additional strands emerged from the literature to generate an eight-strand framework of Culturally Responsive Boarding : building cultural safety in boarding; providing health and wellbeing services; and supporting aspirations. Most of the experiences analysed from the literature were negatively positioned relative to the strands in Culturally Responsive Boarding. The framework is limited because of the dearth of independent evaluations of boarding school outcomes for First Nations students. The proposed framework provides a pragmatic placeholder to support First Nations boarding students and their families until broader reforms happen across the boarding school sector in Australia.